TIEMPOS DE PANDEMIA DEL COVID-19, ACELERACIÓN DIGITAL Y EMPRENDIMIENTOS EN LIMA METROPOLITANA - SUÁREZ ROJAS, Luis (2023)
In this article we explore how people have used digital media and platforms for entrepreneurship and self-employment to resist the COVID-19 pandemic in Metropolitan Lima. In this context, it has been argued that the changes introduced by quarantine, such as remote learning and remote working, require a high dependence on digital media, these changes are here to stay as part of the modus operandi of a system that seeks to reinvent itself in times of crisis